Antitumor Potential and Structure Characterization of Polysaccharides From Lagotis brevituba Maxim in the Tibetan Plateau - Gong, Ruixue; Cao, Weiguo; Huang, Haijun; Yu, Bao; Chen, Huan; Tao, Wei; Luorong, Quji; Luo, Juan; Zhang, Dan (Frontiers in Nutrition, 2022)
This study purified two polysaccharides (LBMPs) from Lagotis brevituba Maxim in several steps. The chemical structure of LBMP-2 was determined by HPGPC, FT-IR, IC, 1H and 13C NMR, AFM, SEM, and TEM. The results show that LBMP-2 was mainly composed by GalA and the Mw of LBMP-2 is 23.799 kDa. In addition, the antioxidant activity and the antitumor activity in vitro and in vivo were studied. LBMP-2 has excellent antioxidant and antitumor capacity. The inhibition of tumor cell proliferation in vitro may result in the inhibition of aerobic respiration and glycolysis. Tumor growth inhibition in vivo may inhibit the expression of AMPK in tumors and enhance spleen function. Compared with conventional chemotherapy drug cyclophosphamide, LBMP-2 is less harmful to the body and safer. Therefore, LBMP-2 provides a potential source of antitumor drugs.